Oral health conditions in patients under antiresorptive therapy are comparable to unexposed during supportive periodontal care - Ciardo, Antonio; Simon, Marlinde M.; Awounvo Awounvo, Junior Sinclair; Kim, Ti-Sun (Clinical oral investigations, 2023)
To investigate oral health and oral health-related quality of life (OHRQoL) of patients under antiresorptive therapy (ART) during supportive periodontal care (SPC) considering history of medication-related osteonecrosis of the jaw (MRONJ).
Im Web of Science ist der DOI fälschlich als 10.1007/s00784-023-05257 angegeben
Gesehen am 23.10.2023